Mempersiapkan Sejak Dini Anak Nagari Minangkabau dalam Memfilter Pengaruh MEA - Irawan, Hendri (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
The Era of the ASEAN Economic Community (MEA) is an ASEAN economic integration in the face of free trade between Southeast Asian countries. For that, the people of Indonesia, especially the Minagkabau community should be able to prepare early younger generation of Minangkabau villages in preparing to face the MEA. The economy needs to be prepared in preparing qualified human resources to create jobs and be ready to work with foreign workers. Cultural aspect First, less understanding of the meaning of kias in Minangkabau culture. Second, Adat basandi syarak, syarak basandi Kitabullah is the cornerstone of the philosophy of the Minangkabau ethnic group in living life. In terms of language, the trend of Indonesian language is being favored by new parents in this Minang land to teach children speak. The occurrence of this mixing will cause the Minangkabau language to disappear from its language users. Especially the young generation who will continue the next struggle. Religion, activating activities back to the surau in instilling religious values. This economic, cultural, linguistic and religious aspect represents the young generation of Minagkabau's capital to win the competition in the Asean Economic Community (MEA) market.